2018
DOI: 10.1021/acs.molpharmaceut.8b00648
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Caffeic Acid Is a Safer Mucosal Adjuvant That Augments Antigen-Specific Mucosal and Systemic Immune Responses in Mice

Abstract: Infections remain a major threat to human lives. To overcome the threat caused by pathogens, mucosal vaccines are considered a promising strategy. However, no inactivated and/or subunit mucosal vaccine has been approved for human use, largely because of the lack of a safe and effective mucosal adjuvant. Here, we show that enzymatically synthesized polymeric caffeic acid (pCA) can act as a potent mucosal adjuvant in mice. Intranasal administration of ovalbumin (OVA) in combination with pCA resulted in the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Nasal-associated lymphoid tissue (NALT) and nasal passages were prepared as previously described [20,21]. Mice that were nasally immunized with CpG ODN-loaded cationic liposomes (10 µg CpG ODN/mouse), OVA (5 µg/mouse), or both (10 µg CpG ODN and 5 µg OVA/mouse) were sacrificed by cervical dislocation, and their NALTs and nasal passages were harvested.…”
Section: Expression Of Il-6 and Transforming Growth Factor-beta (Tgf-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal-associated lymphoid tissue (NALT) and nasal passages were prepared as previously described [20,21]. Mice that were nasally immunized with CpG ODN-loaded cationic liposomes (10 µg CpG ODN/mouse), OVA (5 µg/mouse), or both (10 µg CpG ODN and 5 µg OVA/mouse) were sacrificed by cervical dislocation, and their NALTs and nasal passages were harvested.…”
Section: Expression Of Il-6 and Transforming Growth Factor-beta (Tgf-...mentioning
confidence: 99%
“…OVA-specific antibody titers were evaluated by ELISA, as described earlier [20]. Briefly, a 96-well Nunc MaxiSorp plate (Thermo Scientific, Waltham, MA, USA) was coated with 1.25 µg of OVA (Sigma-Aldrich, St. Louis, MO, USA) in 0.1 M carbonate buffer (pH 9.5) overnight at 4 • C. The plate was then washed with PBS containing 0.05% Tween 20 (PBST) and blocked with 1% bovine serum albumin (BSA; FUJIFILM Wako Pure Chemical Industries) containing PBST (BPBST) at 37 • C for 60 min.…”
Section: Evaluation Of Ova-specific Antibody By Enzyme-linked Immunos...mentioning
confidence: 99%
“…In a previous study, we have reported that intranasal administration of pCA with ovalbumin (OVA), as a model antigen, enhanced OVA-specific antibody production in the mucosal and systemic compartments [25,26]. In this study, we aimed to develop a nasal vaccine against pneumococcal infection using pCA.…”
Section: Nasal Immunization Of a Pspa Antigen With Pca Elicits Pspa-specific Antibody Responses In The Mucosal And Systemic Compartmentsmentioning
confidence: 99%
“…This method resulted in the induction of a higher titer of antigen-specific mucosal and systemic antibody responses in mice. Since intranasal administration of pCA does not exert any toxicity in mice, pCA maybe useful to the development of a safe mucosal vaccine system [25,26]. Further, the sources of CA and HRP are coffee beans and horseradish, respectively, which are easily available.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving phenylpropanoids and coumarin derivatives report caffeic acid as a safe mucosal adjuvant that augments antigen-specific mucosal and systemic immune responses in mice [ 38 ]; cinnamic acid enhances the immunity and upregulates TLR-4 expression by human monocytes…”
Section: Overview On Immunizations With Carrier-plant-phenolics Conjumentioning
confidence: 99%